Development of safe technology of obtaining fatty acid monoglycerides using a new catalyst - Bliznjuk, Olga; Masalitina, Nataliia; Mezentseva, Iryna; Novozhylova, Tetiana; Korchak, Mykola; Haliasnyi, Ivan; Gavrish, Tatiana; Fomina, Iryna; Khalil, Viktoriya; Nikitchenko, Olga (Eastern-European Journal of Enterprise Technologies, 2022)
Fatty acid monoglycerides are a valuable component of the products of various industries. The emulsifying ability of monoglycerides is used in cosmetic, pharmaceutical, and food production. The process of fatty acid monoglycerides obtaining by the reaction of vegetable hydrogenated fat (salomas) with glycerol (glycerolysis method) has been studied. Potassium glycerate is used as a catalyst, which is characterized by high efficiency and safety of production and use. A feature of the work is the study of the dependence of the yield and melting point of monoglycerides on the technological parameters of glycerolysis. As a raw material, hydrogenated refined fat according to DSTU 5040 (CAS Number 68334-28-1) was used: melting point – 48 °C, mass fraction of moisture and volatile substances – 0.08 %, acid value – 0.25 mg KOH/g, peroxide value – 2.8 ½ O mmol/kg. In all experiments, the glycerolysis temperature was 180 °C, the catalyst concentration – 0.5 % in terms of metal. Rational conditions for glycerolysis were determined: duration (90 min.) and glycerol concentration (50 %). Under these conditions, the monoglycerides yield was 32.9 %, melting point – 61.5 °C. The mass fraction of free glycerol in monoglycerides was 1.0 %, acid value – 2.2 mg KOH/g. The efficiency of monoglycerides obtaining using potassium hydroxide and glycerol mixture as a catalyst under certain rational conditions has been studied. The monoglycerides yield of 30.1 %, melting point of 59 °C were obtained. Therefore, the use of potassium glycerate catalyst is more efficient. The results of the study make it possible to improve the technology for the production of fatty acid monoglycerides using a new catalyst and use resources rationally